FACTORS RELATED TO FEMALE COMMERCIAL SEX WORKERS’ ATTITUDES TOWARDS SEXUALLY TRANSMITTED INFECTIONS (STI) PREVENTION - Ahmaniyah Ahmaniyah; Sri Sumarni (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Sexually transmitted infections are still a public health problem in the world, especially in developing countries such as Indonesia. The spread of sexually transmitted infections (STI) among female commercial sex workers cannot be eradicated but may be reduced through prevention efforts. Aims: This study aims to determine the factors related to female commercial sex workers’ attitude towards STI prevention. Methods: This study used quantitative research type with cross sectional approach and purposive sampling to obtain 66 respondents through questionnaire as study instrument.. Data analysis used chi square statistical test. Results: The study revealed that 42.4% was in the young age, 50% had low education level, 54.5% had income more than minimum regional wage, 53% had good knowledge of STI Prevention, 65.2% had support from friends and landlady and 57.6% had good attitude. After the chi square test there was no significant relationship between age, education, income, and friends’ supports to attitude of commercial sex workers toward STI prevention. Knowledge was found as the only variable associated to commercial sex workers’ attitudes toward STI prevention. Conclusion: The study concluded that there was a significant relationship between knowledge and the attitude of respondents in the efforts of STIs prevention.